Takhrij and Syarah Hadith about Chemistry: Content of Miswak for Dental Health - Muhamad Rizki Muttaqin; Weni Luthfiani Fauziah; Citra Fitriani K; Dadang Darmawan; Bambang Qomaruzzaman (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet SAW. about the content of miswak for dental health. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this research is that siwak has many ingredients that are good for dental health. The conclusion of this research is takhrij and syarah hadith of the Prophet SAW. about the content of miswak which is good for dental health that has been recommended by the Prophet SAW.